Variability in cesarean delivery rates among individual labor and delivery nurses compared to physicians at three attribution time points. (26th August 2020) - Edmonds, Joyce K.; Weiseth, Amber; Neal, Brandon J.; Woodbury, Samuel R.; Miller, Kate; Souter, Vivenne; Shah, Neel T.
Abstract: Objective: To examine the variability in the cesarean delivery (CD) rates of individual labor and delivery nurses compared with physicians at three attribution time points. Data Sources: Medical record data from nine hospitals in Washington State from January 2016 through September 2018. Study Design: Retrospective, observational cohort design using an aggregated database of birth records. Data Collection/Extraction Methods: Chart‐abstracted clinical data from a subset of nulliparous, term, singleton, vertex births attributed at admission, labor management, and delivery to nurses and physicians. Two classification methods were used to categorize nurse‐ and physician‐level CD rates at three attribution time points and the reliability of these methods compared. Principal Findings: The sample included 12 556 births, 319 nurses, and 126 physicians. Overall, variation in nurse‐level CD rates did not differ significantly across the three attribution time points, and the extent of variation was similar to that observed in physicians. However, agreement between attribution time points varied between 35 percent and 65 percent when classifying individual nurses into the top and bottom deciles. The average reliability of nurse‐level CD rates was 32 percent at admission (IQR 22.0 percent to 38.7 percent), 32.6 percent at labor (IQR 23.1 percent to 40.9 percent), and 29.3 percent (IQR 20.9 percent to 35.8 percent) at delivery. The average reliability of physician‐level CD rates was higher: 54.2 percent (IQR 38.7 percent to 71.4 percent) at admission, 62.5 percent (IQR 49.0 percent to 79.6 percent) at labor management, and 66.1 percent (IQR 53.7 percent to 81.2 percent) at delivery. Conclusion: Feedback on nurse‐level CD rates as part of routine clinical quality audits can provide insight into nurse performance in the context of other individual‐level and unit‐level information. To reliably distinguish individual nurse performance, larger sample sizes are needed.